PANDANGAN MAHASISWA TERHADAP PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF CLASSPOINT PADA MATA KULIAH PENDIDIKAN AGAMA - Setiyanto, Sigit; Setiawan, Ismail (Jurnal Riset Sistem dan Teknologi Informasi, 2023)
Interactive Learning is a learning method or technique that can be applied with a two-way communication system characterized by interactions between lecturers and students, students and students, and with learning resources in supporting the achievement of learning objectives. Classpoint is an interactive learning application from the company Inknoe that can be integrated with the Microsoft Office PowerPoint presentation application and provides a number of features to create interesting learning materials so as to increase engagement between students and the subject matter. This study aims to determine student perceptions of the use of Classpoint interactive learning media in lecture activities. The approach method used in this research is a descriptive quantitative approach method using a questionnaire. A total of 75 first-semester students in 3 faculties at the University of 'Aisyiyah Surakarta who took the Religious Education course were given a questionnaire containing 16 statements that represented aspects of motivation, usefulness, and cognitive and psychomotor aspects. The student data collected were presented using the percentage of perception questionnaire score criteria. The results showed that the students gave a positive response to the Classpoint interactive learning media with the criteria of strongly agreeing or the response percentage ranging from 86,40% to 94,67%. The positive response given to Classpoint media is due to the presence of several interesting features that support the Classpoint function as an interactive learning medium. The implication of this research is that Classpoint interactive media can be used as a reference for learning media in the classroom, specifically in increasing students' motivation and activeness in learning.